1995
DOI: 10.1002/app.1995.070551003
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime prediction of polymers

Abstract: SYNOPSISNatural and artificially accelerated weathering trials were carried out on low-density polyethylene samples used for agricultural and disposable purposes. Modifications in polymer characteristics were studied using Fourier transform infrared (FTIR) spectroscopy, different scanning calorimetry (DSC), gel permeation chromatography (GPC), scanning electron microscopy (SEM), and mechanical properties testing. The natural exposure trials were conducted at five geographical locations representing varying amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 7 publications
4
37
0
2
Order By: Relevance
“…8,9,22 Hamid and Amin studied both natural and accelerated weathering of low-density polyethylene. 23 They concluded that crosslinking and chain scission reactions occur simultaneously. However, during the initial stages of exposure of WF/HDPE composites to accelerated weathering, crosslinking in the matrix does not predominate.…”
Section: Crystallinity Changes Of Hdpementioning
confidence: 99%
“…8,9,22 Hamid and Amin studied both natural and accelerated weathering of low-density polyethylene. 23 They concluded that crosslinking and chain scission reactions occur simultaneously. However, during the initial stages of exposure of WF/HDPE composites to accelerated weathering, crosslinking in the matrix does not predominate.…”
Section: Crystallinity Changes Of Hdpementioning
confidence: 99%
“…In accelerated weathering, temperatures are elevated above that of the exposure temperatures of natural weathering. Hamid and Amin [14] studied both natural and accelerated weathering of low-density polyethylene (LDPE). They concluded that crosslinking and chain scission reactions take place simultaneously.…”
Section: Crystallinity Changesmentioning
confidence: 99%
“…The degradation reactions therefore occur predominantly in the amorphous region and are controlled by the diffusion of oxygen in this region [10]. While chain scission occurs in the amorphous phase of the polymer, UV-induced crosslinking occurs in imperfect crystalline regions [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variabilidade dos elementos na natureza é o aspecto que mais dificulta a simulação da fotodegradação em laboratório, onde geralmente se utilizam condições padronizadas e controladas. Algumas tentativas de encontrar uma equivalência entre exposições naturais e artificiais foram realizadas e relatadas na literatura [17][18][19][20][21][22][23][24][25][26][27][28][29] , mas os resultados obtidos parecem ser insuficientes para se propor correlações mais abrangentes entre o ambiente e os sistemas de exposição. O tema ainda é muito controverso, carecendo de um maior número de estudos.…”
Section: Introductionunclassified